Happiness and productivity in Ayn Rand’s social and political thought (Economic and Political Thought, 2018)
Ayn Rand is a popular philosopher and political thinker in the UnitedStates. Political thought researchers commonly rank her concepts in the doctrinesof radical liberalism or libertarianism, though Rand herself avoided alldistinctions throughout her life. Rand created her own philosophical school,which she called Objectivism. The school based its philosophy on four values:truth, happiness, reason and justice. These values also became the basis ofRand’s social and political concepts. The purpose of this article is to showhow Rand understood the value of happiness and the virtue of productivity.The philosophical origins of this concept as well as its practical implementationare indicated. Happiness and productivity are ideas that have largelyinfluenced Rand’s and her followers’ anthropological individualism, politicalminarchism and economic laissez-faire.
Keywords: happiness, philosophy, liberalism, libertarianism, Ayn Rand